China's Changing Economic Structures and its Implications for Regional Patterns of Trade Production and Integration - TAN, Kim Song (Institutional Knowledge at Singapore Management University, 2005)
There is tremendous momentum for economic and financial integration in East Asia today. Partly inspired by the formation of the European Union and partly as a response to the 1997/98 Asia financial crisis, many East Asian countries are showing greater commitment to regional economic cooperation. A number of bilateral free trade agreements (FTAs) have either been concluded or are being negotiated.1 At a less formal level, the ASEAN+3 grouping has brought the whole region together in regular consultations over trade, investment, as well as monetary and exchange rate policy matters.